Pengembangan Media Pembelajaran E-Book Pada Mata Kuliah Room Service di Prodi Pendidikan Kesejahteraan Keluarga - Luh Putu Darmiari; Ni Made Suriani; Ida Ayu Putu Hemy Ekayani (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
The new paradigm in the 21st century’s 5.0 is the integration and application of technology in life. One application of this technology is in education.learning designed to adapt to the technological context is expected to provide a unique learning experience for students and lecturers. This research is a developmental research project utilizing technology in the form of e-book development. The purpose of this study to determine the steps in e-book development and the feasibility. The methods is Research&Development (R&D), model 4D approach consistingof four stages: define, design, develop, disseminate. The subjects included media expert validators, material expert validators, and 10 student responden. Data collection techniques used observation, interviews, and quetionnaires to assess e-book feasibility. The results show a percentage of 93,81% of media expert validators with the qualification “Very Eligible” percentage 96.88% by materials experts with the qualification”Very Eligible” and percentage of 93,17% by student responses with the category “Very Eligible” overall the e-book mearning media in the room service course is suitable for use as a mearning medium to support the lecture process. Keywords: Learning Media, E-book, Room Service, 4D